Privatisasi Iklan Konvensional di Ruang Publik - Braniwati, Meutia (Universitas Dinamika, 2025)
Public space is a place that serves to conduct and develop social interactions and plays an important role in maintaining environmental aesthetics. Public space is a place that cannot be separated from the existence of an advertisement. In today's era, advertising development is rampant in both digital and conventional advertising. Conventional advertising is one of the strategies in media to attract audiences in a wide range and in a relatively short time. However, the negative impact that arises is on the public space component, especially advertising in the road or sidewalk area where there is no convention from the local government. Public space is used as a promotional event for both products and services in a conventional manner. This causes a change where public space becomes a privatized space where some advertisers use public space as an economic activity. The research method used is descriptive qualitative analysis to obtain the availability of public space elements and the use of public space related to the use of public space for conventional advertising promotion activities. The findings show that the privatization of conventional advertising in public space will continue to grow from time to time so that an order is needed so that the realization of public space is free from exposure to visual problems including clutter and disorder in urban space. The level of effectiveness, aesthetics, and continuity in the physical dimension of space is also needed because it affects the beauty and comfort of public space. Thus, conventional advertisements in public space areas that are convention in nature need to be considered so that the environment is maintained and problems related to visual waste do not arise.